2016
DOI: 10.1155/2016/2769735
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity and Repair in Rodent Neurotoxic Models of Spinal Motoneuron Disease

Abstract: Retrogradely transported toxins are widely used to set up protocols for selective lesioning of the nervous system. These methods could be collectively named “molecular neurosurgery” because they are able to destroy specific types of neurons by using targeted neurotoxins. Lectins such as ricin, volkensin, or modeccin and neuropeptide- or antibody-conjugated saporin represent the most effective toxins used for neuronal lesioning. Some of these specific neurotoxins could be used to induce selective depletion of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 164 publications
(230 reference statements)
1
2
0
Order By: Relevance
“…This is a simple and straightforward method to investigate the possible occurrence of compensatory changes in both the muscle and spinal cord. The results showed that, following the lesion, the skeletal muscle became atrophic and displayed electromyographic activity similar to that observed in ALS patients [ 96 , 97 , 98 , 99 , 100 ]. CTB-SAP is a prime example of how a single Saporin conjugate can be used in a variety of ways.…”
Section: Behavior Disease and Animal Modelssupporting
confidence: 67%
“…This is a simple and straightforward method to investigate the possible occurrence of compensatory changes in both the muscle and spinal cord. The results showed that, following the lesion, the skeletal muscle became atrophic and displayed electromyographic activity similar to that observed in ALS patients [ 96 , 97 , 98 , 99 , 100 ]. CTB-SAP is a prime example of how a single Saporin conjugate can be used in a variety of ways.…”
Section: Behavior Disease and Animal Modelssupporting
confidence: 67%
“…For instance, in young feline animals, this ability returns spontaneously, while regular training is required for adult cats to accelerate these mechanisms (de Leon et al, 1998). NP mechanisms have also been studied in neurotoxic rodent models of spinal MN disease (Gulino, 2016), where specific neurotoxins were used to induce selective depletion of spinal MN (cholera toxin B), finding plastic changes in the surviving motoneurons. Thus, the manipulation of these surviving MNs could potentially produce a functional restoration, stimulating these MN compensatory mechanisms (Gulino et al, 2019).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Previous studies in our laboratory have shown some mechanisms of SC plasticity in a mouse model of motoneuron depletion induced by intramuscular injection of the retrogradely transported, ribosome-inactivating toxin, cholera toxin-B saporin (CTB-Sap) [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%